2002
DOI: 10.1080/00039420215634
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a ProbioticEnterococcus FaeciumStrain on Selected Bacterial Groups in the Small Intestine of Growing Turkey Poults

Abstract: A feeding trial was carried out with turkey poults, which were fed a diet containing 10(10) viable probiotic E. faecium NCIB 10415 cells/kg feed. Samples of the intestinal tract were analyzed for lactate, colony forming units of total anaerobic bacteria, lactic acid bacteria, enterobacteria and enterococci. Furthermore, metabolic activity of total eubacterial, lactobacilli and enterococci was recorded in selected RNA-extracts with specific ribosomal RNA oligonucleotide probes. Animals fed the probiotic diet sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…Probably, pH value depends on a quantitative proportion of L(+) lactate isomer and D(-) lactate isomer produced by the applied strain. Vahjen et al (2002) also found a significant increase of lactic acid content in the jejunum and ileum of turkeys after the application of Enterococcum faecium. The study of Jin et al (1998) showed that lactobacilli added to the diet of broilers increased the concentrations of volatile fatty acids in the ileum and caecum and decreased the pH values in the caecum.…”
Section: Discussionmentioning
confidence: 77%
“…Probably, pH value depends on a quantitative proportion of L(+) lactate isomer and D(-) lactate isomer produced by the applied strain. Vahjen et al (2002) also found a significant increase of lactic acid content in the jejunum and ileum of turkeys after the application of Enterococcum faecium. The study of Jin et al (1998) showed that lactobacilli added to the diet of broilers increased the concentrations of volatile fatty acids in the ileum and caecum and decreased the pH values in the caecum.…”
Section: Discussionmentioning
confidence: 77%
“…Herranz et al (2001) observed among LAB including some E. faecium strains as nonpathogenic with an ability to produce lactic acid and bacteriocin. In animal management, E. faecium have received more attention as probiotic preparations, such as, in pigs (Macha et al 2004;Scharek et al 2005;Taras et al 2006) and poultry due to having immune system stimulating properties in host and protect animals from gastrointestinal diseases (Taras et al 2006;Vahjen et al 2002). Since E. faecium Pb12 strains survived in the fish intestine without exhibiting the pathogenicity, further experiments were carried out using only this LAB strain among five.…”
Section: Viability Of Bacteria Within Fish Intestinal Milieumentioning
confidence: 99%
“…The use of probiotics for the prevention and treatment of diseases of the intestinal tract in humans (Fuller, 1989;Gorbach, 2000;Marteau & Seksik, 2001;O'Sullivan et al, 2005) and animals (Reuter, 2001;Ghabdan, 2002), especially pigs (Herich et al, 1999;Melin & Wallgren, 2002;Jadamus et al, 2002;Vahjen et al, 2002;Scharek et al, 2005) has become increasingly popular with the knowledge of problems associated with antibiotic use as feed additives (Bengmark, 2000). The benefit of probiotics on the host's intestinal tract is well established (Bocourt et al, 2004;Gibson, 2004;Huang et al, 2004;Marteau et al, 2004), however our knowledge about their mode of action and their influence on the morphology of the intestinal tract is very limited (Jahn, et al, 1996;Görke, 2000;Baum et al, 2002).…”
Section: Introductionmentioning
confidence: 99%